2020
DOI: 10.1038/s41598-020-62223-4
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning-based test for adult sleep apnoea screening at home using oximetry and airflow

Abstract: The most appropriate physiological signals to develop simplified as well as accurate screening tests for obstructive sleep apnoea (OSA) remain unknown. This study aimed at assessing whether joint analysis of at-home oximetry and airflow recordings by means of machine-learning algorithms leads to a significant diagnostic performance increase compared to single-channel approaches. Consecutive patients showing moderate-to-high clinical suspicion of OSA were involved. The apnoea-hypopnoea index (AHI) from unsuperv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 49 publications
1
32
0
1
Order By: Relevance
“…These findings are in accordance with previous studies combining AF-derived features with ODI 3%, which reported not only their complementarity, but also an increase in the diagnostic performance when used together [ 30 , 32 ]. Accordingly, the complementarity of the information from AF and SpO 2 signals in the context of adult OSA [ 34 ] is also confirmed in this study using a pediatric population.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These findings are in accordance with previous studies combining AF-derived features with ODI 3%, which reported not only their complementarity, but also an increase in the diagnostic performance when used together [ 30 , 32 ]. Accordingly, the complementarity of the information from AF and SpO 2 signals in the context of adult OSA [ 34 ] is also confirmed in this study using a pediatric population.…”
Section: Discussionsupporting
confidence: 74%
“…Finally, ODI 3% was computed from the SpO 2 signal as the number of desaturations greater than or equal to 3% from the baseline per hour of recording. This oximetric index has been found useful in previous approaches focused on the detection of childhood OSA [ 25 , 26 , 27 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A bootstrapping procedure was conducted (1000 replicates) to obtain a stable and optimal subset [ 46 ]. The average significance was used as selection threshold T s [ 30 ]. It was computed as the average number of times that all features were selected [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…This stage was conducted following the artifact removal methods proposed in previous studies [ 12 , 17 ]. Signals whose duration was less than 3 h after artifact removal were excluded from our study [ 17 , 30 ]. Moreover, AF signals were normalized to minimize the inter-individual differences related to particular physiological characteristics other than OSA [ 31 ].…”
Section: Databasementioning
confidence: 99%